Des fondements ontologiques de la crise, et de l’être qui pourrait la dépasser - Augustin Berque (VertigO)
The global environmental crisis has been caused by modern civilization, which is ultimately founded on the ontological option of modernity. This option was made in the 17th century, although its roots are ancient. In it, the human being is viewed as being limited to a topos equating the individual person with  the individual body, i.e. as a subject, as opposed to the world, which is viewed as an object. It abstracts this being from the chôra (i.e. from the eco-techno- symbolic milieu), which in fact not only makes our  existence possible, but is also structurally a part of our very Being. This ontological topos makes environmental ethics an oxymoron, entailing all sorts of intellectual acrobatics in order to justify rationally the deep feeling that drives human beings to identify with their environment whereas, in such an option, this identification can only be an irrational projection of the subject onto the object. As a consequence, the entire civilization which this option entailed drives us to indefinitely overuse our environment, which it has reduced to an object, and consume its resources. In the drastic reappraisal which is becoming unavoidable, ethics need first of all an ontological revolution, overcoming the stage of the modern ontological topos, and acknowledging a reality which it had locked out the mediance of the human, that is, the structural coupling of the topos of our individual body with the chôra of our eco-techno-symbolic milieu, through which we can only define our being human. By the same token, mediance drive us to an ethical behaviour toward the Earth as our ecumene, i.e. the ensemble of human environments or milieus, which is not only ecological (as the biosphere is), but eco-techno-symbolic. In short, we need to position environmental ethics ontologically, as an ecumenal ethics.